E-PROCUREMENT MEMODERASI PENGARUH STRATEGI TRANSPARANSI DAN AKUNTABILITAS TERHADAP PENYERAPAN ANGGARAN PENGADAAN BARANG/JASA DI NUSA TENGGARA BARAT - Febriyanti Amol (Journal of Management Small and Medium Enterprises (SMEs), 2021)
The objective of this reaserch is to know and analyze impact of e-procurement on transparancy and accountability strategies for the budget absrorption of goods/services in NTB. The population and sample in this study is the users from all instance in NTB that using e-procurement (specifically e-purchasing based on e-catalogue). In this study did not use samples because all participants became respondents, 30 respondents. The analysis technique is using Multiple Regression Model - Moderated Regression Analysis. The results is the strategy of transparency and accountability has no significant on the absorption of goods/services procurement budgets in NTB. Not only that, E-procurement also can not moderate the transparancy and accountability strategy for the budget absrorption of goods/services in NTB. Keywords: Electronic Procurement, Transparancy, Accountability, Budget Absorption of Goods/Sevices